2022
DOI: 10.7759/cureus.24470
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity and Response to Induction Therapy in Hispanic Patients With Antineutrophilic Cytoplasmic Autoantibody-Associated Vasculitis-Related Diffuse Alveolar Hemorrhage

Abstract: Objectives We examined the response to induction therapy of Hispanic patients with antibody-associated vasculitis (AAV)-related diffuse alveolar hemorrhage (DAH). This study aimed to determine the severity of disease at presentation and the response to induction therapy in our patient population. Methods We retrospectively reviewed the clinical data of Hispanic patients hospitalized with antineutrophil cytoplasmic antibody (ANCA) vasculitis between October 1, 2010, and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Adults comprise a higher proportion of AAV patients than pediatrics [ 81 ]. Thietart et al [ 82 ] evaluated RTX for induction and maintenance therapy in AAV patients older than 75 years. It was shown that RTX induction therapy resulted in remission in 86.4% of patients and the relapse rate was lower when RTX was used as a maintenance regimen compared to induction therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adults comprise a higher proportion of AAV patients than pediatrics [ 81 ]. Thietart et al [ 82 ] evaluated RTX for induction and maintenance therapy in AAV patients older than 75 years. It was shown that RTX induction therapy resulted in remission in 86.4% of patients and the relapse rate was lower when RTX was used as a maintenance regimen compared to induction therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Another study on 251 AAV patients with severe renal disease showed that although RTX and CYC both induce remission in AAV patients, CR was better induced by RTX than CYC [ 98 ]. A study on Hispanic patients showed that RTX and CYC have a similar effect on the induction of remission; however, RTX proved more effective in the prevention of relapse [ 82 ]. Although RTX was found to be as effective as CYC, it was found that RTX is more efficient than Infliximab, an anti-TNF-α agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Loftis et al. study, 19 patients with a diagnosis of DAH associated with ANCA vasculitis were analyzed [ 5 ]. Interesting, GPA was less frequent in this cohort, with only seven patients (37%).…”
Section: Reviewmentioning
confidence: 99%
“…DAH is a feared form of presentation of GPA. DAH is clinically marked by hemoptysis, anemia, diffuse alveolar infiltrates on imaging, and hypoxemic respiratory failure [ 5 ]. The presence of hemosiderin-laden macrophage on bronchoalveolar lavage (BAL) is considered diagnostic [ 6 ].…”
Section: Introductionmentioning
confidence: 99%